May 1, 1973: the anarchists and the popular unity government - Godoy Sepúlveda, Eduardo A. (Cuadernos de Historia, 2013)
Full published the pamphlet “1886 first of May 1973. Day of protest and Social conscience”, distributed in the march of 1° of May 1973 in the city of Santiago by members of the self -styled collective “Groups Anarchists of Chile”.